Assessment of noise level emitted by micro tractor in static and dynamic conditions Avaliação do nível de ruído emitido por um microtrator em condição estática e dinâmica - Elivânia Maria Sousa Nascimento; Carlos Alberto Viliotti; Renildo Luiz Mion; Daniel Albiero; Leonardo de Almeida Monteiro (Semina: Ciências Agrárias, 2013)
Noise is a complex mixture of sounds that causes the feeling of discomfort and is continuously present in the daily lives of human beings. The objective of this study is to assess the noise level emitted by a micro tractor in various situations. In the first situation, the micro tractor is standing still and is subjected to 600, 800, and 1100 rpm from four positions –right, front, left, and rear sides –as well as four distance radii –1, 2, 5, and 10 m. In the second situation, the micro tractor is in motion and is subjected to three operational gears (1st, 2nd, and 3rd) at 1100 rpm with two types of soil surfaces –hard and mobilized. The results reveal that noise levels increase with an increase in the number of engine rotations and they decrease with an increase in the distance radius; this can be observed in all three situations considered in the assessment. Further, it is verified that there is no difference between surfaces in terms of the noise level, and the average value for the hard soil and mobilized soil is 89.5 dB(A) and 91.7 dB(A), respectively. However, for both surfaces, the values are above the threshold of 85 dB(A) for an eighthour work shift. O ruído é um complexo de sons que causam sensação de desconforto e está presente de forma contínua na vida diária dos seres humanos. Objetivou-se com este trabalho avaliar o nível de ruído emitido por um microtrator sob diferentes situações: a primeira com o microtrator parado submetido às rotações de 600, 800 e 1.100 rpm em quatro posições em relação ao microtrator: lados direito, frontal, esquerdo e traseiro e quatro raios de afastamento: 1, 2, 5 e 10 m e a segunda com o microtrator em movimento submetido a três marchas de trabalho (1ª, 2ª e 3ª) a uma rotação de 1.100 rpm em duas superfícies de solo (firme e mobilizado). Os resultados mostraram que o nível de ruído aumenta com um incremento da rotação do motor e diminui à medida que o raio de afastamento aumenta, isso pode ser observado para as três rotações avaliadas. Verificou-se que não há diferenças entre as superfícies, para o nível de ruído, sendo o valor médio para o solo firme de 89,5 dB(A) e de 91,2 dB(A) para o solo mobilizado, mas em ambas as superfícies, os valores estão acima do limite de 85 dB(A) para uma jornada de oito horas.